TATA KELOLA PEMERINTAH YANG INOVAIF DI DESA BULO WATTANG KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Akhyar Akhyar; Herman Dema; Muhammad Rusdi; Jamaluddin Ahmad; Andi Uceng (PRAJA: Jurnal Ilmiah Pemerintahan, 2022)
The purpose of this study is to find out Innovative Governance in Bulo Wattang Village in realizing the principles of Good Governance and sources of innovation organized by the Government in Bulo Wattang Village, Panca Rijang District, Sidenreng Rappang Regency. This study uses a qualitative descriptive approach with data analysis using the Nvivo 12 Plus For Windows application. The results of this study indicate that government governance in the realization of the principles of good governance has not been maximized. The village government does not have a strategic vision and weak enforcement of the rule of law, while the unaccountable BPD has an impact on the low community participation due to weak law enforcement and the lack of The response from the community has resulted in the ineffective and inefficient implementation of the program run by the village government. The village government has not been able to combine the three main elements, namely the government, the village consultative body, and the community in the same commitment. Innovations organized by the village government are limited to instructive innovations and adaptive innovations without independent innovation.